Hypertrophic lichen planus of the vulva - Mouna Korbi; Syrine Ben Ammou; Nour el Imene Ouni; Ahlem Bellalah; Hichem Bel Hadj Ali; J. Zili (Wiley, 2023)
Abstract Vulvovaginal lichen planus is a type of chronic inflammatory dermatosis of the vulva, usually seen as a part of widespread lichen planus. The common clinical types of vulval lichen planus include papulosquamous, erosive, and pigmented types. Hypertrophic lichen planus of the vulva is a rare entity. We report a case of hypertrophic lichen planus of the vulva